Beispiel Nr: 02
$ \text{Gegeben:} \\ \text{Ebene in Koordinatenform: } n_1 x_1+n_2 x_2+n_3 x_3+k1=0 \\ \text{Gesucht:} \\ \text{Hessesche Normalenform} \\ k1<0 \\ \text{HNF:} \dfrac{n_1 x_1+n_2 x_2+n_3 x_3+k_1}{\sqrt{n_1^2+n_2^2+n_3^2}}=0 \\ k1>0 \\ \text{HNF:} \dfrac{n_1 x_1+n_2 x_2+n_3 x_3+k_1}{-\sqrt{n_1^2+n_2^2+n_3^2}}=0 \\ \\ \textbf{Gegeben:} \\ \text{Ebene: } 2 x_1+3 x_2+4 x_3+2=0 \\ \\ \\ \textbf{Rechnung:} \\ \text{Koordinatenform in Hessesche Normalenform HNF} \\ 2 x_1+3 x_2+4 x_3+2=0 \\ \vec{n} = \left( \begin{array}{c} 2 \\ 3 \\ 4 \\ \end{array} \right) \\ \text{Länge des Normalenvektors} \\ \left|\vec{n}\right| =\sqrt{n_1^2+n_2^2+n_3^2} \\ \left|\vec{n}\right| =\sqrt{2^2+3^2+4^2} \\ \left|\vec{n}\right| =5,39 \\ \text{HNF:} \dfrac{2 x_1+3 x_2+4 x_3+2}{-5,39}=0 \\ $